2018
DOI: 10.1016/j.cell.2017.11.048
|View full text |Cite
|
Sign up to set email alerts
|

Selenium Utilization by GPX4 Is Required to Prevent Hydroperoxide-Induced Ferroptosis

Abstract: Selenoproteins are rare proteins among all kingdoms of life containing the 21 amino acid, selenocysteine. Selenocysteine resembles cysteine, differing only by the substitution of selenium for sulfur. Yet the actual advantage of selenolate- versus thiolate-based catalysis has remained enigmatic, as most of the known selenoproteins also exist as cysteine-containing homologs. Here, we demonstrate that selenolate-based catalysis of the essential mammalian selenoprotein GPX4 is unexpectedly dispensable for normal e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
795
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,141 publications
(877 citation statements)
references
References 65 publications
13
795
0
2
Order By: Relevance
“…Incorporation of Sec is energetically expensive; however, the evolutionary advantage of using Sec as opposed to Cys is incompletely understood. Although selenoproteins are considered superior catalysts, it was recently shown that the selenoprotein glutathione peroxidase 4 (GPX4), requires its Sec to prevent irreversible over-oxidation (Ingold et al, 2018). We propose that SelO has evolved a Sec to increase the redox potential of the resulting selenylsulfide bond and/or prevent irreversible over-oxidation, both of which would regulate AMPylation activity.…”
Section: Discussionmentioning
confidence: 99%
“…Incorporation of Sec is energetically expensive; however, the evolutionary advantage of using Sec as opposed to Cys is incompletely understood. Although selenoproteins are considered superior catalysts, it was recently shown that the selenoprotein glutathione peroxidase 4 (GPX4), requires its Sec to prevent irreversible over-oxidation (Ingold et al, 2018). We propose that SelO has evolved a Sec to increase the redox potential of the resulting selenylsulfide bond and/or prevent irreversible over-oxidation, both of which would regulate AMPylation activity.…”
Section: Discussionmentioning
confidence: 99%
“…Our data showed that co-treatment of cells with RSL3 and cisplatin exerted notably improved effect on the inhibition of drug-resistant cells compared with cisplatin treatment alone. Depletion of GPx4 alone is sufficient to induce the ferroptosis of most type of cells in spite of cancer cells, while the enhancement of GPx4 activity is able to protect cells from hydroperoxide-induced ferroptosis (Ingold et al, 2018). Thus, overproduction of ROS induced by cisplatin, in principle, might promote ferroptosis.…”
Section: Discussionmentioning
confidence: 99%
“…As such, glutathione is especially important for the growth and survival of many cancer cells in vitro and in vivo (Harris et al, 2015; Lien et al, 2016; Piskounova et al, 2015). When intracellular GSH levels drop below a critical threshold, the GSH-dependent lipid hydroperoxidase glutathione peroxidase 4 (GPX4) cannot function, which can lead to a fatal buildup of lipid reactive oxygen species (ROS) and cell death via the iron-dependent, non-apoptotic process of ferroptosis (Dixon et al, 2012; Ingold et al, 2018; Yang et al, 2014). De novo GSH synthesis requires cysteine, which is typically found outside cells in the oxidized form as cystine.…”
Section: Introductionmentioning
confidence: 99%